The legal basis for preservation of garden and park art objects - Chernyak, Ihor (Видавництво Львівської політехніки, 2016)
The given research consists in the analysis of legal regulations efficiency concerning issues of garden and park art sites with reference to nature protection laws as compared to national and international monuments protection norms. Проведено аналіз ефективності правового регулювання питань збереження об’єктів садово-паркового мистецтва природоохоронним законодавством порівняно з національними та міжнародними пам’яткоохоронними нормами.
Правові засади збереження об’єктів садово-паркового мистецтва в Україні
Keywords: garden and park arts; cultural heritage; natural reserve fund; садово-паркове мистецтво; культурна спадщина; природно-заповідний фонд